Análisis de los procedimientos para minimizar el riesgo crediticio en las cooperativas de ahorro y crédito reguladas por la Superintendencia de Economía Popular y Solidaria en la Administración Zonal Quitumbe en el sur del D.M.Q. - Saraguro Luzuriaga, Katherine Cristina (2017)
This research aims to analyze if the Savings and Credit Cooperatives regulated by the Superintendence of Popular Economy and Solidarity, located in the Quitumbe Zone in the south of the Metropolitan District of Quito, manage procedures to mitigate credit risk. The study was applied to 17 existing Cooperatives in the sector and authorized Superintendence of Popular and Solidarity Economy, and it was possible to verify that credit risk is always present in all the transactions that with this figure perform the cooperatives, however it depends on the good internal management So that these are mitigated and that the past due portfolio is not maximized in a certain period of time.